Use of topical corticosteroids in dermatology: An evidence-based approach - Anupam Das; Saumya Panda (Wolters Kluwer Medknow Publications, 2017)
Topical corticosteroids (TCs) are the pillars of dermatotherapeutics. These drugs are the "magic molecules," provided they are used judiciously and appropriately, following a rational prescription. On exhaustive literature search in multiple databases, we found a significant evidence favoring the use of TCs in atopic eczema, localized vitiligo, psoriasis, chronic hand eczema, and localized bullous pemphigoid. However, contrary to conventional wisdom, we did not find any high-level scientific evidence in support of prescribing TCs in cutaneous lichen planus, sarcoidosis, and seborrhoeic dermatitis. Besides, evidence clearly advocates judicious use of mild-to-moderate corticosteroids (if required) in pregnancy and lactation and there is no risk of any fetal abnormality.